The Leadership of Shaikh H. Bahruddin Talib Lubis in the Education Sector - Simatupang, Wandana; Mesiono; Asnil Aida Ritonga; Selamat Pasaribu (JTP - Jurnal Teknologi Pendidikan, 2024)
This research aims to answer the problems: (1) To comprehensively analyze the history and struggle of H. Syaikh Bahruddin Talib Lubis in establishing and carrying out his leadership in the field of education in madrasas in particular and the relevance of the education system in North Sumatra to date, (2) Providing color in the education system and development across generations of different ages and periods, as well as providing learning lessons for the importance of strengthening the foundations of educational leadership that cadres and regenerates. This research method uses qualitative library research with a semantic approach, which means that language studies consist of structures to reveal meaning, when meaning is connected to objects in human experience. Meanwhile, the qualitative approach emphasizes descriptive analysis techniques in the qualitative comparison process of literature, regarding the dynamics of relationships between observed phenomena using scientific logic based on observation data, interviews and documentation . Based on the qualitative comparative research process of literature, this research produces results; 1) Implementation of the Leadership of Shaikh H. Bahruddin Talib Lubis in the Education Sector; a) The Shaikh is descended from a prominent and respected family with a strong Islamic religious knowledge by emulating his predecessors, and is loved by the public and admired by his contemporary ulama. b) The Shaikh has visionary leadership, characterized by an education system that is implemented beyond his time. 2) Influence and Leadership Reputation of Sheikh H. Bahruddin Talib Lubis in the Education Sector; a) The Shaykh has a very broad scientific caliber and exceeds the scientific knowledge of the average person of his contemporaries, b) The Shaykh has a firm, consistent and disciplined character. Be tough on those who are wrong and deceitful, soft on people who are committed to education and Islamic teachings. 3) Community Support for the Leadership of Shaikh H. Bahruddin Talib Lubis in the Education Sector; a) The Shaikh is very tolerant and open to accepting suggestions and criticism from society, b) The Shaikh focuses on da'wah and education. preaching personally and organizationally. Educated culturally and institutionally. 4) Strengths and Weaknesses of Sheikh H. Bahruddin Talib's Leadership in the Education Sector; a) Strength, positive character, consistent focus in the mission of preaching and education. Resilient and never giving up from being hit by the problems of the social order of life, b) Weaknesses, cadre formation and regeneration in sustainable education.